Streptomycetes antagonism against Cladosporium fulvum Cooke and Fusarium oxysporium f.sp. lycopersici - Ana Cristina Fermino Soares (Ciência Rural, 2009)
This research aimed to evaluate the secondary effects of secondary metabolites produced by streptomycetes on spore germination and mycelial growth of the phytopathogenic fungi Cladosporium fulvum Cooke and Fusarium oxysporium f. sp. lycopersici from tomato plants. Metabolites produced by streptomycete isolates codified as AC-147 and AC-92 caused 94.1% inhibition of C. fulvum while AC-95 isolate caused 33.9% inhibition. AC-92 was the most efficient for F. oxysporum f. sp. lycopersici, causing 94.2% inhibition of spore germination. For mycelial growth, AC-26 and AC-92 were the most efficient in inhibiting C. fulvum growth by 46.6% and F. oxysporum f. sp. lycopersici by 29.9%. These streptomycetes are potential agents for biocontrol development methods of these tomato plant pathogenic fungi.